1992
DOI: 10.1007/bf00130510
|View full text |Cite
|
Sign up to set email alerts
|

The Sertoli cell in vivo and in vitro

Abstract: The Sertoli cell extends from the basement membrane of the seminiferous tubule towards its lumen; it sends cytoplasmic processes which envelop different generations of germ cells. The use of Sertoli cell culture began to develop in 1975. To reduce germ cell contamination immature animals are generally used as Sertoli cell donors. Sertoli cell mitosis essentially occurs in sexually immature testes in mammals; mitosis of these cells is observed in vitro during a limited period of time. Sertoli cells in vivo perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 21 publications
1
32
0
3
Order By: Relevance
“…Sertoli cells are involved in the formation of the blood-testis barrier and are known to provide nutritional and mechanical support to spermatogenic cells, thereby sustaining normal spermatogenesis 32. In the present study, small seminiferous tubules were associated with disorders of spermatogenesis, corroborating our own earlier findings9 and suggesting a disturbance in the function of Sertoli cells or a decrease in their number as a possible aetiological mechanism for declining sperm counts.…”
Section: Discussionsupporting
confidence: 91%
“…Sertoli cells are involved in the formation of the blood-testis barrier and are known to provide nutritional and mechanical support to spermatogenic cells, thereby sustaining normal spermatogenesis 32. In the present study, small seminiferous tubules were associated with disorders of spermatogenesis, corroborating our own earlier findings9 and suggesting a disturbance in the function of Sertoli cells or a decrease in their number as a possible aetiological mechanism for declining sperm counts.…”
Section: Discussionsupporting
confidence: 91%
“…Omura et al (28) reported that daily doses of 10 mg/kg of TBT affected both testicular development and sperm counts. Jegou (29) found that dysfunction may lead to a reduction in sperm quality and possible infertility. Likewise, Fent and Hunn (30) suggested that TBT can also affect sperm count and male reproductive systems in aquatic organisms.…”
Section: Resultsmentioning
confidence: 99%
“…One of the vital functions of Sertoli cells is phagocytosis of degenerating and apoptotic germ cells and of germ cell material like the so called residual bodies 29 . It is known that residual bodies and cytoplasts from elongated spermatids adhere to isolated Sertoli cells and get phagocytosed 30 .…”
Section: Discussionmentioning
confidence: 99%